'Often in between': Thinking through research methods and Indigenous sovereignty with Yuin Country. Issue 1 (March 2023) - Arnold, Crystal; Atchison, Jennifer; McKnight, Anthony
Indigenous scholars have been calling for renewed attention to the theorisation and practice of sovereignty, including within research. Their scholarship has drawn attention to the sovereignty of people within research processes, as well as diverse expressions of sovereignty. In this article we bring these two dimensions into conversation to consider how research methods might enable and enliven understandings and practices of sovereignty within geography. Illustrating Yuin approaches to research through poetry, observation and dreaming, we show how Country is a living enactment of sovereignty. It dynamically contributes to research processes and enables nonhuman entities to communicate within and beyond their territory as sovereign subjects. In particular, Yuin research methods acknowledge the significant contribution of plants in the theorisation storying and practice of sovereign Country. Through plants, we come to develop a knowledge of sovereign Country as often in between things, including places and knowledges, vulnerability and protection, and removal and persistence. Such insights are respectfully offered here in the spirit of broadening disciplinary perspectives and capacities in order to revitalise research that addresses the relationships between territory and its people.